Formulasi Dan Tantangan Penyelesaian Sengketa Bisnis Persaingan Usaha Tidak Sehat Di Masa Pandemi Covid-19 - Luqman Hakim (Universitas Islam Indonesia, 2021)
During the COVID-19 pandemic, there were business competition legal issues that had broad implications for the public as consumers. The problems of business competition are found in various market sectors in Indonesia including medicines, food, medical devices, education and fuel oil and many more. This study aims to analyze the formulation and challenges of resolving unfair business competition disputes carried out by the Business Competition Supervisory Commission (KPPU) during the covid-19 pandemic. The research method used is a normative juridical method which examines secondary legal materials or literature related to the title of this research. This study concludes that the KPPU's formulation in resolving unfair business competition during the COVID-19 pandemic is the stipulation of KPPU's Regulation No. 1 of 2020 concerning Electronic Case Handling, so that KPPU can enforce the law during the COVID-19 pandemic by utilizing the electronic information system. The challenges faced by KPPU in resolving unfair business competition through electronic media are limited to finding evidence for investigation, investigation and trial. Currently, efforts to find such evidence only rely on the cooperative attitude of the reported party and the reporting party for further legal proceedings. This makes it difficult for KPPU to conduct face-to-face meetings with the reported and the reporting parties because the basis for law enforcement is only through electronic media.Keywords: KPPU; unfair business competition; covid-19 pandemic.AbstrakSelama pandemi covid-19 terdapat permasalahan hukum persaingan usaha yang berimplikasi luas kepada masyarakat selaku konsumen. Permasalahan persaingan usaha tersebut terdapat dalam berbagai sektor pasar di Indonesia diantaranya obat-obatan, pangan, alat kesehatan, pendidikan serta bahan bakar minyak dan masih banyak lagi. Penelitian ini bertujuan untuk menganalisis formulasi dan tantangan penyelesaian sengketa bisnis persaingan usaha tidak sehat yang dilakukan oleh Komisi Pengawas Persaingan Usaha (KPPU) di masa pandemi covid-19. Metode penelitian yang digunakan adalah metode yuridis normatif yang mengkaji bahan hukum sekunder atau kepustakaan terkait dengan judul penelitian ini. Penelitian ini menyimpulkan, formulasi KPPU dalam menyelesaikan persaingan usaha tidak sehat dimasa pandemi covid-19 yaitu ditetapkannya Peraturan KPPU No. 1 Tahun 2020 Tentang Penanganan Perkara Secara Elektronik, sehingga KPPU dapat melakukan penegakan hukum di masa pandemi covid-19 dengan memanfaatkan sistem informasi elektronik. Tantangan yang dihadapi KPPU dalam menyelesaikan persaingan usaha tidak sehat melalui media elektronik yaitu terbatas dalam mencari alat bukti guna penyelidikan, penyidikan maupun untuk persidangan. Saat ini upaya untuk mencari alat bukti tersebut hanya mengandalkan sikap kooperatif terlapor maupun pelapor untuk proses hukum acara selanjutnya, Hal tersebut menyulitkan KPPU melaksanakan pertemuan tatap muka kepada terlapor maupun pelapor karena basis penegakan hukum tersebut hanya melalui media elektronik.Kata Kunci: KPPU; persaingan usaha tidak sehat; pandemi covid-19